2015
DOI: 10.1111/cns.12424
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Topological Organization of Resting‐State Functional Brain Network in Subcortical Vascular Mild Cognitive Impairment

Abstract: Together, our results indicate that svMCI patients exhibit dysregulation of the topological organization of functional brain networks, which has important implications for understanding the pathophysiological mechanism of svMCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 77 publications
2
40
0
Order By: Relevance
“…Previous studies have demonstrated that a disrupted topological organization of nodes is strongly correlated with CI or dementia, but the potential mechanisms are still unclear (Wen et al, 2005;Tuladhar et al, 2015;Yi et al, 2015). Here, we conduct a mediation analysis to further investigate the effect of nodal efficiency on the positive correlation between WMH burden and CI.…”
Section: Mediation Of the Association Between Pwmh And Information Prmentioning
confidence: 93%
“…Previous studies have demonstrated that a disrupted topological organization of nodes is strongly correlated with CI or dementia, but the potential mechanisms are still unclear (Wen et al, 2005;Tuladhar et al, 2015;Yi et al, 2015). Here, we conduct a mediation analysis to further investigate the effect of nodal efficiency on the positive correlation between WMH burden and CI.…”
Section: Mediation Of the Association Between Pwmh And Information Prmentioning
confidence: 93%
“…Similarly, individuals with greater negative correlation between default mode and working memory networks exhibited better behavioural performance on a working memory task (Sala-Llonch et al, 2012). Conversely, in subcortical vascular mild cognitive impairment, increased integration between modules in the inferior and superior parietal gyrus at rest has been shown to be associated with impaired cognitive performance (Yi et al, 2015). Finally, such a broad competitive process is supported by recent work in normative neurodevelopment showing that individuals with weaker sensorimotor integration at rest tended to display better cognitive performance (N = 780 in the Philadelphia Neurodevelopmental Cohort) (Gu et al, 2015).…”
Section: The Benefits Of Independencementioning
confidence: 99%
“…Both structural and functional connectivity contribute independently to healthy cognitive aging (Liem et al, 2017). In older adults with small vessel ischemic disease, worse cognitive control is associated with diminished resting state functional connectivity (RSFC) in the frontoparietal network, default mode network (DMN), and in subcortical structures (Schaefer et al, 2014;Sun et al, 2011;Yi et al, 2015). Despite advances in neuroimaging techniques, the interrelationships among neuroimaging markers of cerebrovascular disease (WMH), structural connectivity, and RSFC, and how these interactions may contribute to age-related changes in cognitive control, is largely unknown.…”
Section: Introductionmentioning
confidence: 99%